STUDENTS' COMPETENCE IN PRONOUNCING ENGLISH IMPERATIVE SENTENCES AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - Firman Amanda; Roswita M. Aboe; Susana R. Bahara (Universitas Khairun, 2023)
This study aims to investigate the competence of third semester students in pronouncing imperative sentences. This research took place at the English Language Education Study Program, Faculty of Teacher Training and Education, University of Khairun Ternate. This study used a descriptive qualitative method to explain and describe students’ competence of the third semester of the English education study program in pronouncing imperative sentences. There were 30 students who participating in this study. The technique data collection used the observation and took audio recording from each student. The technique data analysis used pronunciation application and google translate. It was found out that 22 students (73.33%) obtained excellent score. Then seven students (23.33%) obtained good score. And one student (3.33%) test result is sufficient score. In summary, the average score of students in pronouncing English imperative sentences is excellent with a total average score of 84.74.